Knee osteoarthritis pendulum therapy: In vivo evaluation and a randomised, single-blind feasibility clinical trial - Lixia Huang; Zhidao Xia; Derick Wade; Jicai Liu; Guoyong Zhou; Chuanhua Yu; Helen Dawes; Patrick Esser; Shijun Wei; Jiuhong Song (Journal of Orthopaedic Translation, 2024)
Background: Exercise is recommended as the first-line management for knee osteoarthritis (KOA); however, it is difficult to determine which specific exercises are more effective. This study aimed to explore the potential mechanism and effectiveness of a leg-swinging exercise practiced in China, called ‘KOA pendulum therapy’ (KOAPT). Intraarticular hydrostatic and dynamic pressure (IHDP) are suggested to partially explain the signs and symptoms of KOA. As such this paper set out to explore this mechanism in vivo in minipigs and in human volunteers alongside a feasibility clinical trial. The objective of this study is 1) to analyze the effect of KOAPT on local mechanical and circulation environment of the knee in experimental animals and healthy volunteers; and 2) to test if it is feasible to run a large sample, randomized/single blind clinical trial. Methods: IHDP of the knee was measured in ten minipigs and ten volunteers (five healthy and five KOA patients). The effect of leg swinging on synovial blood flow and synovial fluid content depletion in minipigs were also measured. Fifty KOA patients were randomly divided into two groups for a feasibility clinical trial. One group performed KOAPT (targeting 1000 swings/leg/day), and the other performed walking exercise (targeting 4000 steps/day) for 12 weeks with 12 weeks of follow-up. Results: The results showed dynamic intra-articular pressure changes in the knee joint, increases in local blood flow, and depletion of synovial fluid contents during pendulum leg swinging in minipigs. The intra-articular pressure in healthy human knee joints was −11.32 ± 0.21 (cmH2O), whereas in KOA patients, it was −3.52 ± 0.34 (cmH2O). Measures were completed by 100% of participants in all groups with 95–98% adherence to training in both groups in the feasibility clinical trial. There were significant decreases in the Oxford knee score in both KOAPT and walking groups after intervention (p < 0.01), but no significant differences between the two groups. Conclusion: We conclude that KOAPT exhibited potential as an intervention to improve symptoms of KOA possibly through a mechanism of normalising mechanical pressure in the knee; however, optimisation of the method, longer-term intervention and a large sample randomized-single blind clinical trial with a minimal 524 cases are needed to demonstrate whether there is any superior benefit over other exercises. The translational potential of this article: The research aimed to investigate the effect of an ancient leg-swinging exercise on knee osteoarthritis. A minipig animal model was used to establish the potential mechanism underlying the exercise of knee osteoarthritis pendulum therapy, followed by a randomised, single-blind feasibility clinical trial in comparison with a commonly-practised walking exercise regimen. Based on the results of the feasibility trial, a large sample clinical trial is proposed for future research, in order to develop an effective exercise therapy for KOA.